2016
DOI: 10.2147/ott.s106345
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of <em>hMLH1</em> hypermethylation in non-small-cell lung cancer: a meta-analysis and literature review

Abstract: The hMLH1 gene plays an essential role in DNA repair. Methylation of the hMLH1 gene is common in many types of cancer and can lead to the loss of hMLH1 expression. However, the association and clinicopathological significance between hMLH1 promoter hypermethylation and non-small-cell lung cancer (NSCLC) is elusive. Here, we investigated the correlation of hMLH1 promoter hypermethylation and NSCLC using 13 studies by comprising 1,056 lung cancer patients via a meta-analysis. We observed that 1) loss of hMLH1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…We confirmed that the frequency of hMLH1 promoter methylation in gastric cancer was 7.94-fold higher than that in control groups, meanwhile, the expression of hMLH1 protein substantially decreased in stomach cancer patients with hMLH1 hypermethylation. Our conclusion was similar to some results reported in other types of carcinomas (Mitchell et al, 2002 ; Han et al, 2016 ). hMLH1 promoter methylation often leads to transcriptional silencing accompanied by down-regulation of mRNA expression, resulting in decrease of hMLH1 protein expression and mismatch repair dysfunction which contribute to tumorigenesis.…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed that the frequency of hMLH1 promoter methylation in gastric cancer was 7.94-fold higher than that in control groups, meanwhile, the expression of hMLH1 protein substantially decreased in stomach cancer patients with hMLH1 hypermethylation. Our conclusion was similar to some results reported in other types of carcinomas (Mitchell et al, 2002 ; Han et al, 2016 ). hMLH1 promoter methylation often leads to transcriptional silencing accompanied by down-regulation of mRNA expression, resulting in decrease of hMLH1 protein expression and mismatch repair dysfunction which contribute to tumorigenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Increasing studies have been reported that promoter hypermethylation of tumor suppressor gene may be used as a sensitive marker for NSCLC early diagnosis, prognosis prediction, and potential therapeutic target ( Hulbert et al, 2017 , Feng et al, 2016 , Han et al, 2016 ). In our study, UNC5A is firstly demonstrated as tumor suppressor in the development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been focused on how germline or somatic mutations, as well as promoter methylation, modulate the MLH1 gene, leading to the accumulation of DNA replication errors (7,23). These errors eventually manifest in a high frequency of microsatellite instability (MSI-H).…”
Section: Discussionmentioning
confidence: 99%